PENGARUH RASIO KEUANGAN DAN INVESTMENT OPPORTUNITY TERHADAP FIRM VALUE DIMODERASI FIRM SIZE - Renard Rustanton; Yanti Yanti (Jurnal Paradigma Akuntansi, 2026)
The main purpose of this research is to analyze the effect of profitability, leverage, liquidity, activity and investment opportunity set on the firm value, with firm size as moderating variable on consumer cyclical companies listed on Indonesian Stock Exchange in the period of 2017-2021. This research uses purposive sampling method, and there were 56 companies obtained as samples for this research. The analysis methods in this research are based on multiple regression analysis and moderated regression analysis which are processed using EViews 13 software. Based on the results of this research, the variable leverage and firm size partially had negative and significant effect on firm value. Investment opportunity set partially had a positive and significant effect on the firm value. Profitability, liquidity, and activity partially had no significant effect on firm value. Meanwhile, firm size was able to moderate the effect of profitability, leverage, and activity on the firm value. The implication of this research is that a company has to be active and able to make the right decision because with a high opportunity rate and good decision making, the investors will be more interested in investing on the company which will result in the increase of firm value.